The changing structure of Pakistan's foreign trade - Khusi M. Khan (Intereconomics, 1976)
A high degree of concentration on a few commodities in the export structure of Pakistan during more than a decade of economic planning reflects the typical weakness of many developing countries in generating adequate and stable external resources so badly needed to accelerate their development efforts.
Keywords: 330; Foreign Trade